Locally Advanced Ureteral Cancer Seen in an Ectopic Kidney A Case Report - Maeda, Koki (Hinyokika kiyo. Acta urologica Japonica, 2017)
An ectopic kidney is a common congenital anomaly of the urogenital system, but malignant tumor in an ectopic kidney has been rarely reported. We report a case of ureteral carcinoma arising from an ectopic kidney in an 83-year-old male. He visited a hospital complaining of gross hematuria. Computed tomography revealed right ectopic kidney, right ureteral tumor and bladder tumor around the right ureteral orifice. Transurethral resection of the bladder tumor was performed and histopathological diagnosis was urothelial carcinoma. He was referred to our clinic for surgery of the right ureteral tumor. We performed open right nephroureterectomy and partial cystectomy. The histopathological diagnosis was a high grade urothelial carcinoma of the right ureter, pT3N0. Four months postoperatively, there was no evidence of recurrence. We discuss the clinical and pathological features of the malignancy in an ectopic kidney